Meeting new people : a novel - Lavery, Daniel M. (HarperVia, 2026)
"Fiftysomething, twice-divorced Barbara is at a crossroads. In the midst of her emotional uncertainty, she looks back on the dissolution of the nine best friendships of her life, in hopes of figuring out how to optimize finding her tenth, and hopefully last, best friend. Barbara is acerbic, opinionated, and wrong about many things, but she also doesn't shy away when she's at fault. The turning point of her predicament comes from Barbara's choice, in friends, between (too-young) Caitlyn and the (unsuitable) Other Barbara. Will she repeat the exciting mistakes of the past, or will she try a new kind of mistake for a change? She feels like an out-of-season Scrooge who is unexpectedly, and all at once, surprised and entirely transformed by the possibility of joy."--